'To keep the Devil at bay'? Ephemeral Floor Decoration in Wales during the Nineteenth and Early Twentieth Centuries. (2014) - W, E
Abstract : This paper examines the evidence from Wales for the common but now largely forgotten custom in the late nineteenth and early twentieth centuries of using hearthstone, rubbing stone, or the sap of green leaves to decorate the thresholds, hearths, and floors of farmhouses, cottages, and terraced houses on a daily or weekly basis. It traces the known history of the custom and attempts to place it into the development of homes and housework. The custom was thought by at least some of its practitioners to prevent evil but, whilst the patterns used were ancient, the apogee of the custom may well have post-dated the Industrial Revolution.